Leveraging blockchain technology for cost efficiency of renewable energy - Nwulu, Nnamdi; David, Love; Badrudeen, Tayo Uthman (Frontiers in Energy Research, 2025)
In contributing to reducing the cost of Renewable Energy solutions, this research explores the potential of Blockchain Technology for cost efficiency based on Transaction Cost Theory. The study employed a Systematic Literature Review (SLR) and Bibliometric Analysis using Rayyan and R-programmed Biblioshiny software to collate data from the Scopus and Web of Science databases. The analysis identified the most globally cited documents, trending topics, keyword co-occurrence, and countries of collaboration. The findings revealed blockchain techniques for Renewable Energy cost optimization, including Blockchain-based Auctioning Systems for Renewable Energy Microgrids, Blockchain Levelised Cost of Energy (BLCOE), Smart Contract-oriented Distributed Energy Systems (DES), and the Internet of Energy (IoE) in Renewable Energy Infrastructure and Demand-Side Management. Moreover, the study highlighted factors influencing the cost of renewable energy solutions, such as feed-in tariffs, institutional policy, unfair competitiveness, investment risk, uncertainty, intermittency, and variability. The research concludes that the responsibility for applying blockchain technology lies with the government and Renewable Energy business organizations. Policy recommendations include integrating blockchain in feed-in tariffs, net metering, power purchase agreements, and carbon pricing. Additionally, the study recommends a Smart Contract-oriented International Auctioneering platform for Renewable Energy components and materials.